Blood-Based Liquid Biopsy for Comprehensive Cancer Genomic Profiling Using Next-Generation Sequencing: An Emerging Paradigm for Non-invasive Cancer Detection and Management in Dogs - Kruglyak, Kristina M.; Chibuk, Jason; McLennan, Lisa; Nakashe, Prachi; Hernandez, Gilberto E.; Motalli-Pepio, Rita; Fath, Donna M.; Tynan, John A.; Holtvoigt, Lauren E.; Chorny, Ilya; Grosu, Daniel S.; Tsui, Dana W.Y.; et al. (Frontiers in Veterinary Science, 2021)
This proof-of-concept study demonstrates that blood-based liquid biopsy using next generation sequencing of cell-free DNA can noninvasively detect multiple classes of genomic alterations in dogs with cancer, including alterations that originate from spatially separated tumor sites. Eleven dogs with a variety of confirmed cancer diagnoses (including localized and disseminated disease) who were scheduled for surgical resection, and 5 presumably cancer-free dogs, were enrolled. Blood was collected from each subject, and multiple spatially separated tumor tissue samples were collected during surgery from 9 of the cancer subjects. All samples were analyzed using an advanced prototype of a novel liquid biopsy test designed to noninvasively interrogate multiple classes of genomic alterations for the detection, characterization, and management of cancer in dogs. In 5 of the 9 cancer patients with matched tumor and plasma samples, pre-surgical liquid biopsy testing identified genomic alterations, including single nucleotide variants and copy number variants, that matched alterations independently detected in corresponding tumor tissue samples. Importantly, the pre-surgical liquid biopsy test detected alterations observed in spatially separated tissue samples from the same subject, demonstrating the potential of blood-based testing for comprehensive genomic profiling of heterogeneous tumors. Among the 3 patients with post-surgical blood samples, genomic alterations remained detectable in one patient with incomplete tumor resection, suggesting utility for noninvasive detection of minimal residual disease following curative-intent treatment. Liquid biopsy allows for noninvasive profiling of cancer-associated genomic alterations with a simple blood draw and has potential to overcome the limitations of tissue-based testing posed by tissue-level genomic heterogeneity.